$\begin{array}{1 1}3/8 \\ 1/8 \\ 1/4 \\ 5/8 \end{array} $

Want to ask us a question? Click here

Browse Questions

Ad |

0 votes

0 votes

- P (not A and not B) = \(P(\bar{A}\cap\;\bar{B})\) = \(P(\overline{A \cup B})\) = 1 - P (A $\cup$ B)
- P (A $\cup$ B) = P(A) + P(B) - P(A $\cap$ B)
- P (\(\bar{A})\) = 1 - P(A)

Given \(\;P(A)=\large \frac{1}{4}\), \(P(B)=\large \frac{1}{2}\) and \(\;P(A\cap\;B)=\large \frac{1}{8}\)

P (A $\cup$ B) = P(A) + P(B) - P(A $\cap$ B)

\(\Rightarrow \;P(A\cup\;B)=\large \frac{1}{4}+\frac{1}{2}-\frac{1}{8}\) =\(\large\;\frac{5}{8}\)

\(\Rightarrow P(\bar{A}\cap\;\bar{B})=1-P(A\cup\;B)\) =\(\;1-\large\frac{5}{8}=\frac{3}{8}\)

Ask Question

Take Test

x

JEE MAIN, CBSE, AIPMT Mobile and Tablet App

The ultimate mobile app to help you crack your examinations

...